If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x^3-2x^2+5x-5=(x2+x+4)(3x+1)+6
We move all terms to the left:
3x^3-2x^2+5x-5-((x2+x+4)(3x+1)+6)=0
We do not support expression: x^3
| 90=42+2x | | -2x2+110x=900 | | 12+5+n=45 | | 6^x-14*6^-x=5 | | 6^x-14*6-x=5 | | B2+12b+21=10 | | 4x+13=-29-20x | | 0.25x-0.125=0.875=0.5x | | x+1/x=3/7 | | x+1/x=7/3 | | x/x+1=3/7 | | -7-2n=12+n-7-6 | | 6/12=10/x | | 21/50=x/400 | | -4k-6(-3k+7)=-112 | | 4x+8x+16=12 | | 8+5x+2x=36 | | 12-2x=6x-108 | | 7(x+2)^2=35 | | 4,y=-4 | | 49-4x=14-8x | | 1(x-3)^2+-6=0 | | 2x+15-3x=0 | | 5x2+8x-23=0 | | 6x/2-8=15/2 | | 30=12u-6u | | 6x/2-8=14/2 | | 12u-6u=0 | | 6x/4-8=13/2 | | 6x/3-8=11/2 | | 100=1.03x | | A=2b+1.03b |